Black in the British Frame: The Black Experience in British Film and Television - Bourne, Stephen (Bloomsbury Publishing Plc, 2005)
In this updated edition of his acclaimed and award-winning study, Stephen Bourne takes a personal look at the history of black people in popular British film and television. He documents, from original research and interviews, the experiences and representations which have been ignored in previous media books about people of African descent. There are chapters about Paul Robeson, Newton I. Aduaka, soap operas and much more - as well as several useful appendices and suggestions for further reading.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Pour une autre histoire du cinéma français : blanchité et maghrébinité de la francité - Derfoufi, Mehdi (De l'autre côté, 2019)
Parution dans la revue Diogène d’un article co-écrit avec James Berclaz-Lewis. En dépit de la publication de travaux importants depuis les années 1990, le champ disciplinaire des études ciném…
Keywords: 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _À vérifier-Cinéma

Contemporary Jewish Reality in Germany and Its Reflection in Film - Dorchain, Claudia Simone; Wonnenberg, Felice Naomi (De Gruyter, 2012)
The notion of “self” and “other” and its representation in artwork and literature is an important theme in current cultural sciences as well as in our everyday life in contemporary Western societies. Moreover, the concept of “self” and “other” and its imaginary dichotomy is gaining more and more political impact in a world of resurfacing ideology-ridden conflicts. The essays deal with Jewish reality in contemporary Germany and its reflection in movies from the special point of view of cultural sciences, political sciences, and religious studies. This anthology presents challengingly new insights into topics rarely covered, such as youth culture or humor, and finally discusses the images of Jewish life as realities still to be constructed.
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Postcolonial/Décolonial: La preuve par l'art - Toussaint, Évelyne (Presses universitaires du Midi, 2021)
"Les liens entre l'art contemporain et les questions de colonialité, postcolonialité, et décolonialité sont anciens et multiples. Des artistes occidentaux et non-occidentaux, depuis plusieurs décennies déjà, s'en sont emparés pour produire des œuvres qui témoignent de leurs engagements politiques, sociétaux et esthétiques. Des concepts que les études postcoloniales ont approfondies ou inventées – agency (agentivité), mimicry (mimétisme/simulacre), ou essentialisme stratégique –, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination, sont ainsi revisités par les artistes. D'autre part, des auteurs, relevant de ces champs d'études qui conservent aujourd'hui toute leur actualité politique et leur pertinence théorique, disent à leur tour l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art présente des travaux portant sur des démarches artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, des artistes du collectif Mira au Mexique, Iris Kensmil, Jean Renoir, et bien d'autres), mais aussi sur des propositions institutionnelles (notamment initiées par le Centro de Arte y Comunicación de Buenos Aires, la Biennale de Venise ou le Van Abbemuseum d'Eindhoven), associées en de nouveaux réseaux de solidarités. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales. Sous un angle historiographique et épistémologique, on trouvera ici des analyses des fondements historiques, théoriques et idéologiques du postcolonial dont les théorisations, loin de la saturation conceptuelle dont certains veulent les accuser, concernent particulièrement l'histoire de l'art. "
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Geralt of Poland: The Witcher 3 Between Epistemic Disobedience and Imperial Nostalgia - Majkowski, Tomasz Z. (Open Library of Humanities, 2018)
This article is a reading of The Witcher 3 in relation to postcolonial approaches to Polish culture. It departs from an analysis of an online debate on racial representation in the game as a possible act of epistemic disobedience, and moves on to a consideration of three narrative aspects of the game itself: its representation of political struggle, the ideological stance of the protagonist, and ethnic inspirations in worldbuilding. By referring those three issues to postcolonial analyses of Polish culture, as well as Walter D. Mignolo’s concept of decolonization through epistemic disobedience, this article aims to demonstrate paradoxical qualities of the game, which tries to simultaneously distance itself from the established, West-oriented ways of knowledge production and gain recognition as an artifact of modern Western pop culture. Moreover, it employs the tradition of Polish Romanticism to establish itself as a bridge between Slavdom and Western culture, and strengthen the colonial idea of Poland being the proper ruler over Slavs.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Virtual Worlds, Digital Dreams - Šisler, Vít (Digital Middle East: state and society in the information age, 2018)
Video games are inherently transnational by virtue of their industrial, textual and player practices. Until recently, the focus of research on the social and cultural aspects of video games has been on the traditional centers of the video game industry consumption, while the international flows of digital gaming remained largely underexplored. This chapter analyzes the cultural dynamics and technological processes influencing both video game development and the gaming culture in the Middle East. It conceptualizes Middle Eastern video games as imaginary spaces that entangle diverse and contradictory processes: global cultural flows, media policies of nation states, visions and engagements of private entrepreneurs, and migration and appropriation of Western game genres and rule systems. By mapping out dominant trends, the chapter offers the opportunity to think about processes and flows influencing the video game industry in the Middle East during the first fifteen years of its existence
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digital Arabs: Representation in Video Games - Šisler, Vít (European Journal of Cultural Studies, 2008)
This article presents the ways in which Muslims and Arabs are represented and represent themselves in video games. First, it analyses how various genres of European and American video games have constructed the Arab or Muslim Other. Within these games, it demonstrates how the diverse ethnic and religious identities of the Islamic world have been flattened out and reconstructed into a series of social typologies operating within a broader framework of terrorism and hostility. It then contrasts these broader trends in western digital representation with selected video games produced in the Arab world, whose authors have knowingly subverted and refashioned these stereotypes in two unique and quite different fashions. In conclusion, it considers the significance of western attempts to transcend simplified patterns of representation that have dominated the video game industry by offering what are known as 'serious' games.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé